2007
DOI: 10.1152/ajplung.00286.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of the congenital diaphragmatic hernia-inducing teratogen nitrofen

Abstract: Congenital diaphragmatic hernia (CDH) is a developmental anomaly that results in significant mortality and morbidity. The underlying etiology is poorly understood. Insights will arise from an understanding of the mechanisms by which the teratogen nitrofen induces CDH in rodent models. In this study, we use in vitro cell assays in conjunction with whole animal rodent studies to test hypotheses regarding nitrofen's mechanism of action. The first component examined the interaction of nitrofen with various aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 68 publications
0
65
0
Order By: Relevance
“…In vitro experiments have demonstrated that several agents (including nitrofen) responsible for the induction of diaphragmatic hernias, inhibit RALDH2 activity [71,72] . Others have proposed that nitrofen interferes with the uptake of retinol by lung cells.…”
Section: Nitrofen Modelmentioning
confidence: 99%
“…In vitro experiments have demonstrated that several agents (including nitrofen) responsible for the induction of diaphragmatic hernias, inhibit RALDH2 activity [71,72] . Others have proposed that nitrofen interferes with the uptake of retinol by lung cells.…”
Section: Nitrofen Modelmentioning
confidence: 99%
“…A number of candidate genes are involved in the retinoic acid pathway (Montedonico et al, 2008;Klaassens et al, 2009). Previous research using animal models has demonstrated that environmental factors including a vitamin A-deficient (VAD) diet or exposure to teratogenic agents, particularly nitrofen, can disrupt the retinoid signalling pathway resulting in CDH (Wilson et al, 1953;Thebaud et al, 1999;Babiuk et al, 2004;Oshiro et al, 2005;Nakazawa et al, 2007a,b;Noble et al, 2007;Clugston et al, 2010). Further evidence of the involvement of this pathway comes from knockout or mutant mouse models in which genes involved in retinoid signalling are shown to cause CDH when silenced, including compound null retinoic acid receptor (RAR) mutants which were shown to have a spectrum of VAD-like defects including diaphragm defects (Lohnes et al, , 1995Mendelsohn et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The primordial diaphragm development arises from four different structures: septum transversum, pleuroperitoneal folds, dorsal mesentery and elements from the thoracic body wall [5,6] . Several theories have been proposed to explain primary embryologic events leading to CDH, including failure of closure of the pleuroperitoneal canals, defective myoblast formation or abnormal phrenic nerve innervation [7][8][9] . In animal models, CDH arises from a malformation of the amuscular mesenchymal substratum of the pleuroperitoneal folds before pleuroperitoneal canal closure [10,11] .…”
mentioning
confidence: 99%
“…The development of the diaphragm strongly depends on the role of proteins associated with the metabolism and binding of retinoids [47,48] . The nitrofen rat model has particularly highlighted the importance of retinoic acid (RA) in the diaphragm development, but this model has also provided limited insights into understanding the genetic basis of CDH [9] . Retinoids play a central role in many biological processes, particularly during embryogenesis and lung development [49][50][51][52][53] .…”
mentioning
confidence: 99%